Endoscopic decompression as management of uncomplicated sigmoid volvulus: case report and literature review - Agustin, Blaz-Zavala R.; Alejandra, Sanchez-Escobar; Antonio, Espinosa-Nader Jose; Renata, Diez-Gonzalez; César , Reyes-Elizondo (International Journal of Research in Medical Sciences, 2024)
Sigmoid volvulus is a cause of intestinal obstruction explained by the twist of the sigmoid over its mesentery. The colon is at risk of ischaemia due to alterations in the irrigation due to rotation of the mesentery and risk of perforation. Surgical management is suggested in complicated cases, but endoscopic management with decompression and detorsion may be suggested in the case of uncomplicated sigmoid volvulus, with risk of recurrence. We present the case of a 49-year-old male with a diagnosis of uncomplicated sigmoid volvulus resolved by decompression with rigid proctosigmoidoscopy and medical management with remission of intestinal occlusion, without surgical intervention. A case and review of the current literature are presented.